2009
DOI: 10.1038/nature07953
|View full text |Cite
|
Sign up to set email alerts
|

Autism genome-wide copy number variation reveals ubiquitin and neuronal genes

Abstract: Autism spectrum disorders (ASDs) are childhood neurodevelopmental disorders with complex genetic origins1 -4. Previous studies focusing on candidate genes or genomic regions have identified several copy number variations (CNVs) that are associated with an increased risk of ASDs5 -9. Here we present the results from a whole-genome CNV study on a cohort of 859 ASD cases and 1,409 healthy children of European ancestry who were genotyped with ~550,000 single nucleotide polymorphism markers, in an attempt to compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,094
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,311 publications
(1,148 citation statements)
references
References 29 publications
35
1,094
2
17
Order By: Relevance
“…In some instances, neuropsychiatric disorders such as autism and schizophrenia are postulated to result from genetic mutations in these neuronal cell-adhesion systems. 27,28 Recent discoveries now indicate that acquired autoimmune syndromes also target trans -synaptic signals. Leucine-rich glioma-inactivated 1 (LGI1) is a secreted protein that interacts with presynaptic ADAM23 and postsynaptic ADAM22 to create a trans -synaptic protein complex, which also includes potassium channels and AMPA-type glutamate receptors.…”
Section: Autoimmune Synaptic Encephalitismentioning
confidence: 99%
“…In some instances, neuropsychiatric disorders such as autism and schizophrenia are postulated to result from genetic mutations in these neuronal cell-adhesion systems. 27,28 Recent discoveries now indicate that acquired autoimmune syndromes also target trans -synaptic signals. Leucine-rich glioma-inactivated 1 (LGI1) is a secreted protein that interacts with presynaptic ADAM23 and postsynaptic ADAM22 to create a trans -synaptic protein complex, which also includes potassium channels and AMPA-type glutamate receptors.…”
Section: Autoimmune Synaptic Encephalitismentioning
confidence: 99%
“…1,2 Recent studies have demonstrated that ASDs can be caused by rare, highly penetrant point mutations, deletions, duplications and larger chromosomal abnormalities that can either arise de novo or be inherited. [3][4][5][6][7][8][9] Known monogenic disorders account for 2-5% of syndromic cases; fragile X syndrome is usually the most common cause, followed by PTEN macrocephaly syndrome and tuberous sclerosis, each accounting for o1% of individuals with ASD. 1,10 Large copy number variants (CNVs) are found in 5-10% of autistic patients, especially in those with syndromic ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,13 Private CNVs in individuals with autism often disrupt genes encoding synaptic proteins, such as neuroligins, neurexins and SHANK proteins, or neuronal cell-adhesion proteins, which have important roles in neurodevelopment and/or neurotransmission. 3,[14][15][16][17] However, most CNVs and variants in genes involved in autism so far are also found in other neurodevelopmental disorders such as ID without autistic features and/or schizophrenia. 12,18 Recent studies point to polygenic or oligogenic inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have yielded some exciting results for several diseases, such as schizophrenia and autism. [56][57][58] Therefore, it further supports the use of CNVs as genetic markers to uncover new susceptibility loci for future disease association studies. Interestingly, genome-wide homozygosity mapping approaches have also been applied to dissect the genetic basis of complex diseases and have successfully identified a number of susceptibility loci for schizophrenia.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 83%